Free Market 4.0 & Karnival Keusahawanan 2023 / Ong Sheau Fen - Ong, Sheau Fen (Academy of Language Studies, 2023)
On 12-13 January 2023, the Free Market 4.0 and Karnival Keusahawanan 2023 charity and entrepreneur events were held. The Malaysian Academy of SME and Entrepreneurship Development (MASMED) of Universiti Teknologi MARA Cawangan Pulau Pinang set the theme of Berkongsi Rezeki Tanda Kesyukuran to denote the importance of sharing sustenance. Thirteen faculties and departments from UiTM Cawangan Pulau Pinang (UiTMCPP) set up stalls where the public could obtain preloved items for free. The Academy of Language Studies (ALS) was represented by a team consisting of Seng Hui Zanne, Melati Desa, Wan Noorli Razali, Isma Noornisa Ismail, Nur Husna Serip Mohamad, Aileen Farida Mohd Adam, Marni Jamil, Nur Ilianis Adnan, Che Nooryohana Zulkifli, Noraziah Mohd Amin, Nazima Versay Kudus, and Ong Sheau Fen. On Thursday, January 12th, items were placed at the stalls between 8am and 10am, with the members in charge drawing in the crowd to obtain the products. The stall was also visited by the Rector, Assoc. Prof. Ir. Dr. Haji Ahmad Rashidy Razali. The event continued to attract the crowd on Friday, with donated items from department members, such as clothes, toys, books, kitchenware, accessories, shoes, plants, bags, and CDs proving to be quite popular. By the end of the two-day event, all of the donated items had been almost entirely cleared out. This event was a great success, thanks to the collaborative efforts of everyone who participated and the invaluable support from the management.